Implementation of Project CBISp-EDP (Communicate, Build and Intensify Stakeholders’ Participation- Exemplified and Deepened Partnership) and External Stakeholders’ Participation (International Journal of Theory and Application in Elementary and Secondary School Education, 2023)
The study mainly focused on assessing the implementation of Project CBISp-EDP and external stakeholders’ participation in Calamba Bayside Integrated School. The study utilized a descriptive correlational research design. The respondents of the study were the 80 teachers and 99 parents of CBIS. Teacher-respondents were identified using a simple random sampling technique, while purposive sampling was used to identify the parent-respondents. Results of the study revealed that all teachers have the same level of observation in implementing Project CBISp-EDP. It also showed that external stakeholders participated in most school-initiated activities. Moreover, it also disclosed that the implementation of Project CBISp-EDP has a significant relationship with external stakeholders’ participation. It is recommended that the school consider the crafted action plan to strengthen stakeholders’ participation further.